2016
DOI: 10.15580/gjeph.2016.2.082116131
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Views on Knowledge and Barriers to Cervical Cancer Screening among Women in Kaduna State, Nigeria

Abstract: Cervical cancer is a major cause of death among women in Kaduna State. Knowledge and access to regular screening will reduce the incidence of the disease. This study was a community-based, qualitative study on women living in Kaduna State, Nigeria. It assessed women`s knowledge about cervical cancer screening and identified barriers affecting screening for cervical cancer among women in Kaduna State. The population of the study included women of reproductive age group between 15 and 45 years who were purposive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…9 Specifically, the prevalence of cervical cancer screening in Nigeria has been reported at rates of 8.3%, 28 0%, 29 5.2%, 30 10.2%, 9 15%, 31 4.4%, 11 and 18.4%. 16 Furthermore, it has been reported that almost two-thirds of patients with cervical cancer in Nigeria and other developing countries present at stages III or later, 9,10,22,26,27,32 and that a single one time screen could potentially save the lives of more than 6,000 women annually. 9 This calls for the proper education of the populace on the benefits of cervical cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…9 Specifically, the prevalence of cervical cancer screening in Nigeria has been reported at rates of 8.3%, 28 0%, 29 5.2%, 30 10.2%, 9 15%, 31 4.4%, 11 and 18.4%. 16 Furthermore, it has been reported that almost two-thirds of patients with cervical cancer in Nigeria and other developing countries present at stages III or later, 9,10,22,26,27,32 and that a single one time screen could potentially save the lives of more than 6,000 women annually. 9 This calls for the proper education of the populace on the benefits of cervical cancer screening.…”
Section: Introductionmentioning
confidence: 99%